Psychoanalysis, artistic obsession, and artistic motivation: the study of pathography. - Kemler, David S (Perceptual and Motor Skills, 2014)
A modern assessment of Freud's conceptualization of the creative process focusing on drives, ego psychology, and object relation theory is presented. 40 artists and musicians were interviewed employing 13 open-ended questions to provoke responses historically associated with the theoretical conceptualizations of Freud and post-Freudian theory related to the creative process. Creative process was defined as internal object relations that motivate the external connection between artist and the creative work. Measured responses concerning purpose and understanding; motivation before, during, and after performance; obstacles in performance; and needs through the creative process were assessed. Cluster analysis segregated the participants into high, medium, and low agreement groups based on similarity of responses. A multivariate stepwise regression revealed four questions (enlightenment, drives, obstacles, and ought self discrepancies) accounted for 83.9% of the variance. A post hoc discriminant function analysis identified 82.5% of the population to their correct groups. The findings support Spitz's (2005) suggestion that we regard “drives, ego psychology, and object relation theory not as separate approaches but as parts of a whole with varying stresses or accents” (p. 503).
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/012-434-150-540-250 tex.type: [object Object]
Keywords: Adult; Art; Cluster Analysis; Creativity; Drive; Female; Freudian Theory; Humans; Male; Middle Aged; Motivation; Multivariate Analysis; Music; Object Attachment; Obsessive Behavior; Psychoanalytic Theory; Regression Analysis; adult; art; article; cluster analysis; creativity; dept.hms; drive; female; human; male; middle aged; motivation; multivariate analysis; music; object relation; obsession; psychoanalytic theory; psychological aspect; regression analysis

Seeing to hear? Patterns of gaze to speaking faces in children with autism spectrum disorders. - Irwin, Julia R; Brancazio, Lawrence (Frontiers in Psychology, 2014)
Using eye-tracking methodology, gaze to a speaking face was compared in a group of children with autism spectrum disorders (ASD) and a group with typical development (TD). Patterns of gaze were observed under three conditions: audiovisual (AV) speech in auditory noise, visual only speech and an AV non-face, non-speech control. Children with ASD looked less to the face of the speaker and fixated less on the speakers' mouth than TD controls. No differences in gaze were reported for the non-face, non-speech control task. Since the mouth holds much of the articulatory information available on the face, these findings suggest that children with ASD may have reduced access to critical linguistic information. This reduced access to visible articulatory information could be a contributor to the communication and language problems exhibited by children with ASD.
23 citations (Crossref) [2023-10-31] Place: Switzerland Irwin, Julia R. Haskins Laboratories New Haven, CT, USA ; Department of Psychology, Southern Connecticut State University New Haven, CT, USA. Brancazio, Lawrence. Haskins Laboratories New Haven, CT, USA ; Department of Psychology, Southern Connecticut State University New Haven, CT, USA.
Keywords: Audiovisual speech perception; Autism spectrum disorders; Communication development; Eyetracking; Lipreading; Speech in noise; dept.hls; dept.hms; dept.psy; peer-reviewed